(untitled) (Global Journal of Computer Science and Technology, 2019)
With the ever changing dynamic environment in mobile devices, mobile software applications need to cope with some particular performance environment that include the limited resources, high autonomy requirements and mark et regulations among other constraints [1]. To provide a software development process that responds to these challenges, adoption of Agile methodology that follows an iterative approach to build software rapidly where the entire software development lifecycle is brok en down into smaller iterations helps to minimize overall risk s. This allows software projects developed though agile methodologies to be easily modified rapidly to meet the users/customers2019; requirements. This paper assesses the development of mobile applications in the agile software development environment.